Adsorption of Ammonia Nitrogen in Aqueous Solution Using Zeolite A - P Assawasaengrat; R Rueangdechawiwat (My University, 2019)
Abstract The capacity of alternative adsorbents including rice straw, delignified rice straw and zeolite A for ammonia nitrogen removal from aqueous solution was investigated. The adsorption experiments were carried out in batch system with initial ammonia nitrogen concentration of 0.5 mg-N/l, 1000 ml ammonia nitrogen solution for 1 g of adsorbent. Experimental data indicated that rice straw and delignified rice straw cannot adsorb ammonia nitrogen. However, zeolite A provided rapidly adsorption capacity for ammonia nitrogen removal. The amount of ammonia nitrogen adsorbed by zeolite A was 0.256 mg/g at 1 minute after the experiment was initially conducted and slightly stable at 0.275 mg/g after 10 minutes. The adsorption experiments were carried out at 0.25, 0.5, 1.0, 2.0, 4.0, and 8.0 mg-N/l of ammonia nitrogen concentration. The results indicated that zeolite A had the adsorption capacity of 0.102, 0.294, 0.551, 1.153, 2.303, and 3.897 mg/g respectively at equilibrium time. The Langmuir and Freundlich adsorption models were applied to describe the equilibrium isotherms. Based on R 2 , Freundlich model was more promising to represent the adsorption data than Langmuir model.
Keywords: Langmuir adsorption model; Phosphorus and nutrient management